Phlaeothripidae (Thysanoptera) diversity in Australia, with three new generic records and two new species - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2022)
The genera Ponticulothrips, Trichinothrips and Tylothrips are newly recorded from Australia. Litotetothrips symplocosae sp.n. is described as the fourth species from Australia of this Asian genus, and Ponticulothrips mudloi sp.n. is described as the second known species in this genus that was previously known only from Japan. Trichinothrips and Tylothrips are each represented in Australia by single species, each of which is known from several countries.